A Knowledge Economy Assessment of Qatar - World Bank (Washington, DC, 2012)
This knowledge economy assessment of Qatar ranks it using the following indices: the Knowledge Economy Index (KEI), Knowledge Index, Economic Incentive and Institutional Regime, Education, Innovation and Information Infrastructure (ICT). The assessment compares Quatar to the rest of the 131 countries in the Knowledge Assessment Methodology (KAM). In more detail, it is compared to Finland, Kuwait, Saudi Arabia, Singapore and United Arab Emirates. Qatar s current KEI is 5.83. It ranks higher than the average for MENA (5.06) and the World (5.59). It ranks lower than the regional average for Western Europe (8.32). It has improved since 1995, when it was 5.52. The regional average for MENA has fallen, from 5.31 in 1995. Among comparators, Finland has the highest KEI, at 9.12. The Comparator UAE has the lowest KEI, at 4.95. Qatar is strongest on the ICT pillar it ranks nearly at the 66th percentile. It is weakest on education pillar it ranks at the 52nd percentile. It has improved significantly on innovation pillar, and regressed on the EIR, education and ICT pillars, compared to 1995.